Fiber membrane for promoting healing of infected wounds and preparation method and application thereof

By using fiber membranes prepared by levopolylactic acid materials, combined with electrospinning and inorganic nanoparticles, the problem of unsatisfactory synergistic treatment of bacterial infection and wound healing in the prior art is solved, and efficient antibacterial and wound healing effects are achieved.

CN119083028BActive Publication Date: 2025-04-29PEKING UNIV SCHOOL OF STOMATOLOGY +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410656488.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-07-24
Filing Date
2024-05-24
Publication Date
2025-04-29
Estimated Expiration
2044-05-24

AI Technical Summary

Technical Problem

The existing skin wound treatment plan has not been ideal for synergistic treatment of bacterial infection and wound healing, and there are problems such as low drug utilization, increased bacterial resistance, poor stability, single treatment methods, and reduced treatment effects.

Method used

Fibrous membranes are prepared by levopolylactic acid materials, and multiple non-randomly arranged spinning nanofibers are prepared through electrospinning technology, and inorganic nanoparticles are added to the fiber membrane to promote wound healing through antibacterial, relieving inflammation, collagen regeneration and angiogenesis.

Benefits of technology

Effective antibacterial and wound healing for bacterial infections have been achieved. The fiber membrane has excellent surface flexibility, wound adaptability, antibacteriality and wound healing ability, and can maximize the antibacterial and tissue repair functions without adding external drugs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119083028B_ABST
    Figure CN119083028B_ABST
Patent Text Reader

Abstract

The present invention discloses a fiber membrane that promotes the healing of infected wounds, a preparation method and an application thereof. The fiber membrane includes a plurality of non-randomly arranged spinning nanofibers, which are prepared by electrostatic spinning from a material including L-polylactic acid. The porous microstructure of the fiber membrane of the present invention provides a suitable microenvironment for cell migration and epithelial regeneration, and can promote the healing of bacterial-infected wounds. It has been verified that the fiber membrane of the present invention can effectively promote wound healing through antibacterial, relieving inflammation, collagen regeneration and angiogenesis. In addition, the present invention can maximize the antibacterial and tissue repair functions without adding external drugs through ultrasound enhanced treatment, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to application number 202310906012X, filed on July 24, 2023, entitled “Methods and Applications for Improving Piezoelectric Properties of Polylactic Acid Fiber Films,” the contents of which are incorporated herein by reference in their entirety. Technical Field

[0003] The invention belongs to the field of biomedical materials, and in particular relates to a fiber membrane for promoting healing of infected wounds and a preparation method and application thereof. Background Art

[0004] Skin wound healing is a complex and dynamic biological phenomenon, and changes in the local microenvironment are an important reason for unsuccessful wound healing. Bacterial invasion and infection of skin wounds can destroy the internal microenvironment and induce inflammation, thereby hindering the healing process.

[0005] At present, common treatments for skin wounds include: (1) drug therapy, which is a common method for treating skin wound healing, using topical drugs or antibiotics. However, drug therapy has problems such as low drug utilization, increased bacterial resistance, poor stability, single treatment method, and reduced treatment effect; (2) negative pressure wound therapy (NPWT), which acts on the wound surface after debridement on a regular and intermittent basis, can quickly increase blood flow to the wound surface, promote the entry of new blood vessels into the wound surface, stimulate the growth of granulation tissue, achieve adequate drainage, reduce edema, reduce infection, and inhibit bacterial growth. However, poor mechanical pressure regulation and infection control of the wound surface can cause discomfort to patients; (3) wound dressings, which are usually made of natural or synthetic polymer materials, can simulate the structure and function of human tissue, isolate the wound from exogenous pathogens, prevent water loss, and provide an ideal microenvironment for wound healing. They are standard wound treatment methods in clinical and daily life, but have poor healing effects, high infection risks, and poor antibacterial properties.

[0006] This shows that the existing skin wound treatment regimen has unsatisfactory synergistic therapeutic effects on bacterial infection and wound healing. Summary of the invention

[0007] In order to solve at least some of the problems in the above-mentioned prior art, the present invention uses poly-lactic acid (PLLA) material to prepare a fiber membrane, and verifies that it can effectively resist bacterial infection and promote wound healing through antibacterial, inflammation relief, collagen regeneration and angiogenesis. Specifically, the present invention includes the following contents.

[0008] In a first aspect, the present invention provides a fiber membrane for resisting bacterial infection and promoting wound healing, which comprises a plurality of non-randomly arranged spun nanofibers, wherein the spun nanofibers are prepared by electrostatic spinning from a material comprising L-lactic acid.

[0009] In certain embodiments, according to the fiber membrane for resisting bacterial infection and promoting wound healing of the present invention, the material further comprises inorganic nanoparticles, wherein the inorganic nanoparticles are selected from at least one of barium titanate, barium strontium titanate, strontium titanate, lithium niobate and potassium sodium niobate.

[0010] In certain embodiments, according to the fiber membrane for resisting bacterial infection and promoting wound healing of the present invention, the receiving end of the spinning is a roller, and the non-random arrangement is achieved by controlling the rotation speed of the receiving roller, and the rotation speed is 2000-5000 rpm.

[0011] The second aspect of the present invention provides a method for preparing a fiber membrane for resisting bacterial infection and promoting wound healing, which comprises the following steps:

[0012] (1) dissolving L-polylactic acid in an organic solvent to obtain a L-polylactic acid solution;

[0013] (2) using the L-polylactic acid solution to perform electrospinning to obtain a fiber membrane; and

[0014] (3) Annealing the fiber membrane.

[0015] In certain embodiments, the preparation method according to the present invention further comprises, before step (2), a step of dispersing inorganic nanoparticles in the poly (L-lactic acid) solution.

[0016] In certain embodiments, according to the preparation method of the present invention, the concentration of the inorganic nanoparticles in the poly (L-lactic acid) solution is 5-9 wt %.

[0017] In certain embodiments, according to the preparation method of the present invention, the annealing treatment comprises: first annealing the fiber membrane at 100-110°C for 8-12 hours, naturally cooling to room temperature, and then annealing at 155-165°C for 8-12 hours and then naturally cooling to room temperature.

[0018] In certain embodiments, the preparation method according to the present invention further comprises a step of ultrasonically treating the fiber membrane after step (3).

[0019] In certain embodiments, according to the preparation method of the present invention, the effective sound intensity during ultrasonic treatment is controlled to be 0.20-2.50 W / cm 2, the ultrasonic frequency is 0.5-4 MHz.

[0020] The third aspect of the present invention provides the use of the fiber membrane according to the first aspect of the present invention in the preparation of anti-bacterial infection materials, wound dressings, and repair materials for promoting tissue regeneration.

[0021] A fourth aspect of the present invention provides a medical device, which includes the fiber membrane of the present invention and an ultrasonic generator.

[0022] In certain embodiments, according to the medical device of the present invention, the effective sound intensity that the ultrasonic generator can generate is 0.20-2.50 W / cm 2 , the ultrasonic frequency is 0.5-4 MHz.

[0023] In a fifth aspect of the present invention, a method for improving the performance of a fiber membrane is provided, wherein the fiber membrane is the above-mentioned fiber membrane, and the method comprises subjecting the fiber membrane to ultrasonic treatment, and preferably the ultrasonic treatment conditions include: an effective sound intensity of 0.20-2.50 W / cm 2 , ultrasonic frequency is 0.5-4 MHz, and pulse treatment is more preferred.

[0024] In certain embodiments, according to the method for improving the performance of a fiber membrane according to the present invention, an annealing treatment is performed before the ultrasonic treatment.

[0025] In certain embodiments, according to the method for improving the performance of a fiber membrane of the present invention, the annealing treatment comprises: first annealing the fiber membrane at 100-110°C for 8-12 hours, naturally cooling it to room temperature, and then annealing it at 155-165°C for 8-12 hours and then naturally cooling it to room temperature.

[0026] The fiber membrane of the present invention has excellent surface flexibility, wound adaptability, antibacterial properties and the ability to promote wound healing. Its porous microstructure provides a suitable microenvironment for cell migration and epithelial regeneration, and can promote the healing of bacterially infected wounds. It has been verified that the fiber membrane of the present invention can effectively promote wound healing through antibacterial, inflammation relief, collagen regeneration and angiogenesis. In addition, the present invention can maximize the antibacterial and tissue repair functions without adding external drugs through ultrasound enhanced treatment, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1Characterization of BaTiO3 / PLLA electrospun fiber membranes, where Flat represents cast membranes, BTR represents electrospun fiber membranes with randomly arranged fibers, and BTA represents electrospun fiber membranes with oriented fibers. (A) HR-TEM image of BaTiO3 / PLLA electrospun fiber membranes, with a scale of 100 nm; (B) quantification of diameter of BaTiO3 / PLLA electrospun fibers with oriented fibers; (C) quantification of diameter of BaTiO3 / PLLA electrospun fibers with randomly arranged fibers; (D) X-ray diffraction (XRD) pattern of BaTiO3 / PLLA electrospun fiber membranes; (E) tensile strength of BaTiO3 / PLLA electrospun fiber membranes; (F) water contact angle of BaTiO3 / PLLA EFMs.

[0028] Figure 2 The d of each group of membranes is shown 33 value.

[0029] Figure 3 Figure 2 shows the piezoelectric properties of BaTiO3 / PLLA electrospun fiber membrane under ultrasonic irradiation, where (A) is the output voltage of BaTiO3 / PLLA electrospun fiber membrane, (B, C) are the piezoelectric properties of BaTiO3 / PLLA electrospun fiber membrane under ultrasonic irradiation, and (B, C) are the piezoelectric properties of BaTiO3 / PLLA electrospun fiber membrane for detecting •OH and •O2 - (D, E, F) are the electron spin resonance spectra of 5,5-dimethyl-1-pyrroline-n-oxide (DMPO) with different signal, and (D, E, F) are the UV-visible absorption spectra of Rhodamine B solution in Flat and BaTiO3 / PLLA electrospun fiber membranes after ultrasonic stimulation for different times.

[0030] Figure 4 The in vitro antibacterial treatment of Staphylococcus aureus and Escherichia coli by BaTiO3 / PLLA electrospun fiber membrane, where (A) is a representative SEM image of Staphylococcus aureus and Escherichia coli grown on BaTiO3 / PLLA electrospun fiber membrane, with a scale bar of 500 nm; (B, E) are quantitative analysis of the antibacterial rate of Staphylococcus aureus and Escherichia coli by live / dead staining; (C, F) are quantitative analysis of protein leakage of Staphylococcus aureus and Escherichia coli grown on BaTiO3 / PLLA electrospun fiber membrane; (D, G) are evaluations of biofilm formation after co-culture with the material under ultrasonic irradiation by crystal violet staining; (H) is an image of biofilm formation after co-culture with BaTiO3 / PLLA electrospun fiber membrane evaluated by live and dead bacterial staining, with a scale bar of 200 μm.

[0031] Figure 5 Live-dead staining images of Staphylococcus aureus and Escherichia coli after co-culture with BaTiO3 / PLLA electrospun fiber membranes. The scale bar is 100 nm.

[0032] Figure 6Figure 3 shows the in vitro biocompatibility of BaTiO3 / PLLA electrospun fiber membranes. (A) is the live / dead staining image of L929 cells after co-culture with BaTiO3 / PLLA electrospun fiber membranes, with a scale bar of 100 nm; (B) is a representative image of L929 cell migration experiment at different times, with a scale bar of 200 nm; (C) is the quantitative results of CCK-8 at 1, 2, and 3 days in different groups; (D) is the quantitative analysis of the migration rate of L929 cells after co-culture with BaTiO3 / PLLA electrospun fiber membranes.

[0033] Figure 7 The results show that (A) is the timeline of the healing process of the skin defect mouse model infected with Staphylococcus aureus; (B) is the photos of the skin infected with Staphylococcus aureus at different times, with a scale bar of 1 mm; (C) is the wound traces during the healing process; (D) is the quantitative analysis of wound closure; (E) is a representative image of HE staining results on the 10th day, with scale bars of 500 μm and 200 μm, respectively; (F) is the quantitative statistics of inflammatory cells on the 10th day; (G) is a representative image of Masson's trichrome staining results on the 10th day, with scale bars of 500 μm and 200 μm, respectively; (H) is the quantitative statistics of collagen deposition.

[0034] Figure 8 The figures are in vivo immunofluorescence analysis and comparison of the same type of anti-infection healing and repair effects, wherein (A) is a representative immunofluorescence image of iNOS (green), KRT5 (red), and CD31 (pink) co-stained on the infected wound surface on the 10th day, and the cell nucleus stained with DAPI (blue), and the scale bar is 200 μm; (BD) are the calculation of the average fluorescence intensity to indicate the protein expression level; (EG) is the quantitative analysis of TNFα, iNOS and IL-1β mRNA expression; (H) is a comparison of the membrane material prepared by the present invention with the same type of membrane material. DETAILED DESCRIPTION

[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0036] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that the upper and lower limits of the scope and each intermediate value therebetween are specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art to which the invention belongs. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0038] Fiber membrane

[0039] One aspect of the present invention provides a fiber membrane for resisting bacterial infection and promoting wound healing, wherein the fiber membrane comprises a plurality of non-randomly arranged spun nanofibers, and the spun nanofibers are prepared by electrostatic spinning from a material comprising L-polylactic acid. In some cases, the fiber membrane is an ultrasonically driven fiber membrane, and ultrasonic drive means that when ultrasonic stimulation or ultrasonic irradiation or ultrasonic generator treatment is performed, the fiber membrane has an enhanced effect of resisting bacterial infection and promoting wound healing. In some cases, the fiber membrane is a fiber membrane that has been annealed twice before ultrasonic treatment, and the two annealing treatments are described in detail below.

[0040] In the present invention, "bacteria" refers to any bacteria that can cause skin wound infection, examples of which include but are not limited to Staphylococcus aureus, Escherichia coli, Enterococcus, Streptococcus, Pseudomonas aeruginosa, etc.

[0041] In the present invention, "non-random arrangement" and "directional arrangement" and "regular arrangement" can be used interchangeably, which means that multiple fibers are arranged in parallel or substantially parallel manner. The non-random arrangement is achieved by controlling the rotation speed of the receiving drum. The inventors have found through research that the rotation speed of the receiving drum affects the arrangement characteristics and electrical properties of the fibers in the fiber membrane, and further affects the antibacterial properties. If the rotation speed of the receiving drum is too low, the fiber orientation deteriorates, and the fibers in the fiber membrane tend to be randomly arranged or disorderly arranged, with poor electrical properties and affecting its antibacterial properties. On the other hand, if the rotation speed of the receiving drum is too high, it will affect the mechanical properties of the fiber membrane, such as causing a decrease in tensile strength. In a preferred embodiment, the rotation speed of the receiving drum is 2000-5000 rpm, preferably 2000-4800 rpm, also preferably 2000-4600 rpm, further preferably 2000-4400 rpm, more preferably 2000-4200 rpm, more preferably 2000-4000 rpm, more preferably 2000-3800 rpm, more preferably 2000-3600 rpm, more preferably 2000-3400 rpm, more preferably 2000-3200 rpm, more preferably 2000-3000 rpm, for example 2000, 2100, 2200, 2300, 2400, 2500, 2600, 2700, 2800, 2900, 3000 rpm.

[0042] In the present invention, the diameter of the spun nanofiber is 100-500 nm, preferably 110-450 nm, further preferably 120-400 nm, further preferably 130-350 nm, more preferably 140-300 nm, more preferably 150-250 nm, for example 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250 nm.

[0043] In a preferred embodiment, the material of the fiber membrane of the present invention further includes inorganic nanoparticles. The inorganic nanoparticles form a uniform dispersion and interface combination in the fiber membrane, which can immediately generate an electric field and an electret with high storage charge stability, and can produce cavitation effect and mechanical effect under ultrasonic treatment, which can stimulate cell migration and sterilization.

[0044] In a preferred embodiment, the inorganic nanoparticles are selected from at least one of barium titanate, barium strontium titanate, strontium titanate, lithium niobate and potassium sodium niobate. In a most preferred embodiment, the inorganic nanoparticles are barium titanate. The particle size of the inorganic nanoparticles is not particularly limited, for example, it can be 10-200 nm, preferably 20-150 nm, further preferably 50-150 nm, and further preferably 80-120 nm, for example 80, 90, 100, 110, 120 nm.

[0045] In the present invention, the thickness of the fiber membrane is 1-250 μm, preferably 50-200 μm, further preferably 50-100 μm, such as 50, 60, 70, 80, 90, 100 μm.

[0046] The polylactic acid nanofiber membrane of the present invention can manage wound exudate well, and provide a porous microstructure to simulate a more suitable matrix microenvironment to promote wound healing. The fiber membrane produces reactive oxygen species (ROS) under ultrasound, further reducing the selective permeability of bacterial cell membranes, targeting internal nucleic acids, and ultimately achieving the effects of antibacterial, reducing inflammation, and promoting wound healing. In a mouse model of infected skin, the fiber membrane played a key role in reducing infection and promoting wound skin tissue regeneration. The skin regeneration process was further evaluated by indicators such as inflammation, collagen deposition, angiogenesis, and re-epithelialization. The results showed that the fiber membrane of the present invention can effectively resist bacterial infection and promote skin healing.

[0047] Preparation method

[0048] One aspect of the present invention provides a method for preparing a fiber membrane for resisting bacterial infection and promoting wound healing, which comprises the following steps:

[0049] (1) dissolving L-polylactic acid in an organic solvent to obtain a L-polylactic acid solution;

[0050] (2) performing electrospinning to obtain a fiber membrane;

[0051] (3) Annealing the fiber membrane.

[0052] In step (1), the L-polylactic acid is uniformly dissolved in an organic solvent at a concentration of 5-15%, preferably 6-12%, and also preferably 6-11% (e.g., 6, 7, 8, 9, 10, 11%), wherein the organic solvent is not particularly limited, as long as it can dissolve the L-polylactic acid, and examples thereof include but are not limited to dioxane, trifluoroethanol, dimethylformamide, tetrahydrofuran, isopropanol, halogenated methane such as dichloromethane, trichloromethane, difluoromethane, trifluoromethane, dichloroethane, trichloroethane, difluoroethane, trifluoroethane. In a preferred embodiment, the organic solvent is trifluoroethanol.

[0053] In a preferred embodiment, the preparation method of the present invention, before step (2), further comprises the step of dispersing inorganic nanoparticles in a L-polylactic acid solution, wherein the concentration of the inorganic nanoparticles in the L-polylactic acid solution should not be too large or too small, as too large or too small concentrations will affect the mechanical and electrical properties of the fiber membrane, thereby affecting the antibacterial properties. In a preferred embodiment, the concentration of the inorganic nanoparticles in the L-polylactic acid solution is 5-9 wt%, preferably 5.2-8.8 wt%, further preferably 5.4-8.6 wt%, further preferably 5.6-8.4 wt%, more preferably 5.8-8.2 wt%, more preferably 6.0-8.0 wt%, for example 6.0, 6.2, 6.4, 6.8, 7.0, 7.2, 7.4, 7.6, 7.8, 8.0 wt%.

[0054] In step (2), the process conditions of electrospinning are not particularly limited and can be adjusted as needed. Preferably, the process conditions of electrospinning are: voltage is 10-30 kV, preferably 10-28 kV, also preferably 10-26 kV, further preferably 10-24 kV, more preferably 10-22 kV, more preferably 10-20 kV, for example 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 kV; receiving distance is 10-30 cm, preferably 10-28 cm, also preferably 10-26 cm, further preferably 10-24 cm, more preferably 10-22 cm, more preferably 10-20 cm, for example 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 cm.

[0055] In step (3), the annealing treatment is a double annealing treatment, which includes: the fiber membrane is first subjected to a first annealing treatment at 100-110°C (e.g., 100, 101, 102, 103, 104, 105, 106, 107, 108, 109, 110°C) for 8-12 hours (e.g., 8, 9, 10, 11, 12 hours), and then naturally cooled to room temperature, and then subjected to a second annealing treatment at 155-165°C (e.g., 155, 156, 157, 158, 159, 160, 161, 162, 163, 164, 165°C) for 8-12 hours (e.g., 8, 9, 10, 11, 12 hours), and then naturally cooled to room temperature. The first annealing treatment is used to obtain a β-phase crystal form, and the subsequent second annealing further stabilizes the material in the specific crystal form.

[0056] In order to better disperse the dispersed inorganic nanoparticles and dope them in the fibers, the method of the present invention further includes a step of pretreating the inorganic nanoparticles, which pretreatment step includes: dispersing the inorganic particles in a sodium citrate solution and stirring, then taking the precipitate after centrifugation or sedimentation, adding anhydrous ethanol and stirring, then adding deionized water and stirring, taking the precipitate after centrifugation or sedimentation and vacuum drying, and the drying temperature is 40-70°C, preferably 50-60°C.

[0057] The method of the present invention further comprises: (4) treating the fiber membrane by ultrasound. The ultrasound treatment can be performed using an ultrasound generator known in the art, and is not particularly limited thereto.

[0058] application

[0059] One aspect of the present invention provides the use of a fiber membrane capable of resisting bacterial infection and promoting wound healing in the preparation of anti-bacterial infection materials, wound dressings, and repair materials for promoting tissue regeneration.

[0060] One aspect of the present invention provides use of a fiber membrane and an ultrasonic generator combination in preparing a device for improving biological functions.

[0061] In a preferred embodiment, the ultrasonic generator can generate an effective sound intensity of 0.20-2.50 W / cm 2 , preferably 0.40-2.30 W / cm 2 , preferably 0.60-2.10 W / cm 2 , further preferably 0.80-1.90 W / cm 2 , for example 0.80, 0.90, 1.00, 1.10, 1.20, 1.30, 1.40, 1.50, 1.60, 1.70, 1.80, 1.90 W / cm 2 The ultrasonic frequency is 0.5-4 MHz, preferably 0.5-3.5 MHz, also preferably 0.5-3 MHz, further preferably 0.5-2.5 MHz, more preferably 0.5-2.0 MHz, for example 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 MHz.

[0062] In the present invention, the ultrasound generated by the ultrasonic generator is continuous ultrasound or pulsed ultrasound. Preferably, the ultrasound is pulsed ultrasound, which has a stronger fiber performance improvement effect than continuous ultrasound and further biological functions (including anti-bacterial infection and / or wound healing performance) generated thereby. When pulsed ultrasound is performed, the pulse duration is 1-10 ms, preferably 2-8 ms, and further preferably 2-6 ms, such as 2, 3, 4, 5, 6 ms, and the total output is 5-20 min, preferably 5-15 min, such as 5, 6, 7, 8, 9, 10 min.

[0063] Methods for improving fiber membrane performance

[0064] In one aspect of the present invention, a method for improving the performance of a fiber membrane is also provided, and the fiber membrane performance includes but is not limited to the mechanical properties, electrical properties, anti-bacterial infection properties and wound healing performance of the obtained fiber membrane. In a preferred embodiment, the method is particularly suitable for a fiber membrane having a non-random arrangement of nanofibers prepared by electrospinning from a material including L-polylactic acid. In another preferred embodiment, the method is particularly suitable for a fiber membrane having a non-random arrangement of nanofibers prepared by electrospinning from a material including L-polylactic acid and nano inorganic particles. For ultrasonic treatment and annealing of the fiber membrane, refer to the aforementioned content and will not be repeated here.

[0065] Example 1

[0066] This example illustrates a method for preparing a fiber membrane.

[0067] BaTiO3 particles were dispersed in deionized water containing 2% w / v sodium citrate. Stirred at ambient temperature for 12 h, observed for stratification after 30 min, and then discarded the supernatant. Next, 30 mL of anhydrous ethanol was added and stirred for 30 min to form a stratified supernatant, which was repeated twice. Then deionized water was added and stirred for 30 min, and then the supernatant was separated and discarded until there was no obvious turbidity in the supernatant. The residue was thoroughly dried at 55 °C in a vacuum oven. At the same time, L-polylactic acid powder was uniformly dissolved in trifluoroethanol at a concentration of 10%. Subsequently, BaTiO3 nanoparticles were ultrasonically dispersed in L-polylactic acid and trifluoroethanol solutions at a concentration of 7 wt% and stirred for 12 h to form a uniform suspension. This suspension was then used to prepare electrospun nanofiber membranes. The electrospinning device used a 22 g metal injection needle with the needle tip 15 cm away from the center of the roller group. A static voltage of 15 kV was applied between the two. The roller receiver rotated at 2800 rpm and the spinning was completed after 8 h.

[0068] After spinning, the membrane was placed in a drying oven at room temperature for 24 hours, then annealed at 105 °C for 10 hours, annealed at 160 °C for 10 hours, and then cooled to room temperature. The parameters of low-intensity pulsed ultrasound loading were: operating frequency 1 MHz, effective sound intensity 1 W / cm 2 When pulse ultrasound is performed, the pulse duration is 4ms and the total output is 10 min.

[0069] Example 2

[0070] This example illustrates a method for preparing a fiber membrane.

[0071] BaTiO3 particles were dispersed in deionized water containing 2% w / v sodium citrate. Stirred at ambient temperature for 12 h, observed for stratification after 30 min, and then discarded the supernatant. Next, 30 mL of anhydrous ethanol was added and stirred for 30 min to form a stratified supernatant, which was repeated twice. Then deionized water was added and stirred for 30 min, and then the supernatant was separated and discarded until there was no obvious turbidity in the supernatant. The residue was thoroughly dried at 55 °C in a vacuum oven. At the same time, L-polylactic acid powder was uniformly dissolved in trifluoroethanol at a concentration of 10%. Subsequently, BaTiO3 nanoparticles were ultrasonically dispersed in L-polylactic acid and trifluoroethanol solutions at a concentration of 7 wt% and stirred for 12 h to form a uniform suspension. This suspension was then used to prepare electrospun nanofiber membranes. The electrospinning device used a 22 g metal injection needle with the needle tip 15 cm away from the center of the roller group. A static voltage of 15 kV was applied between the two. The roller receiver rotated at 2800 rpm and the spinning was completed after 8 h.

[0072] After spinning, the membrane was placed in a drying oven to dry at room temperature for 24 h, then annealed at 105 °C for 10 h, annealed at 160 °C for 10 h, and then cooled to room temperature.

[0073] Comparative Example 1

[0074] This comparative example illustrates a method for preparing a fiber membrane.

[0075] BaTiO3 particles were dispersed in deionized water containing 2% w / v sodium citrate. Stirred for 12 h at ambient temperature, observed the stratification after resting for 30 min, and then discarded the supernatant. Next, 30 mL of anhydrous ethanol was added and stirred for 30 minutes to form a stratified supernatant, which was repeated twice. Then deionized water was added and stirred for 30 minutes, and then the supernatant was separated and discarded until there was no obvious turbidity in the supernatant. The residue was thoroughly dried at 55 °C in a vacuum oven. At the same time, the L-polylactic acid powder was uniformly dissolved in trifluoroethanol at a concentration of 10%. Subsequently, BaTiO3 nanoparticles were ultrasonically dispersed in the L-polylactic acid and trifluoroethanol solution at a concentration of 7 wt% and stirred for 12 h to form a uniform suspension. This suspension was then used to prepare electrospun nanofiber membranes. The electrospinning device used a 22 g metal injection needle with the needle tip 15 cm away from the center of the roller group. A static voltage of 15 kV was applied between the two. The roller receiver rotated at 300 rpm and the spinning was completed after 8 h.

[0076] After spinning, the membrane was placed in a drying oven at room temperature for 24 hours, then annealed at 105 °C for 10 hours, annealed at 160 °C for 10 hours, and then cooled to room temperature. The parameters of low-intensity pulsed ultrasound loading were: operating frequency 1 MHz, effective sound intensity 1 W / cm 2 When pulse ultrasound is performed, the pulse duration is 4ms and the total output is 10 min.

[0077] Comparative Example 2

[0078] This comparative example illustrates a method for preparing a fiber membrane.

[0079] BaTiO3 particles were dispersed in deionized water containing 2% w / v sodium citrate. Stirred for 12 h at ambient temperature, observed the stratification after resting for 30 min, and then discarded the supernatant. Next, 30 mL of anhydrous ethanol was added and stirred for 30 minutes to form a stratified supernatant, which was repeated twice. Then deionized water was added and stirred for 30 minutes, and then the supernatant was separated and discarded until there was no obvious turbidity in the supernatant. The residue was thoroughly dried at 55 °C in a vacuum oven. At the same time, the L-polylactic acid powder was uniformly dissolved in trifluoroethanol at a concentration of 10%. Subsequently, BaTiO3 nanoparticles were ultrasonically dispersed in the L-polylactic acid and trifluoroethanol solution at a concentration of 7 wt% and stirred for 12 h to form a uniform suspension. This suspension was then used to prepare electrospun nanofiber membranes. The electrospinning device used a 22 g metal injection needle with the needle tip 15 cm away from the center of the roller group. A static voltage of 15 kV was applied between the two. The roller receiver rotated at 300 rpm and the spinning was completed after 8 h.

[0080] After spinning, the membrane was placed in a drying oven to dry at room temperature for 24 h, then annealed at 105 °C for 10 h, annealed at 160 °C for 10 h, and then cooled to room temperature.

[0081] Comparative Example 3

[0082] The pure solution of PLLA was cast into a film with a thickness of 60 μm and then dried at 50°C. The parameters of low-intensity pulsed ultrasound loading were: working frequency 1 MHz, effective sound intensity 1 W / cm2, pulse duration 4 ms, and a total output of 10 min.

[0083] Comparative Example 4

[0084] The pure solution of PLLA was cast into a film with a thickness of 60 μm and then dried at 50° C. No ultrasound was applied.

[0085] Comparative Example 5

[0086] The difference between the preparation method of this comparative example and that of Example 1 is that after spinning, the membrane is placed in a drying oven and dried at room temperature for 24 hours, then annealed at 105°C for 10 hours and then cooled to room temperature. The loading parameters of low-intensity pulsed ultrasound are: operating frequency 1 MHz, effective sound intensity 1 W / cm 2 When pulse ultrasound is performed, the pulse duration is 4ms and the total output is 10 min.

[0087] Comparative Example 6

[0088] The difference between the preparation method of this comparative example and that of Example 1 is that after spinning, the membrane is placed in a drying oven at room temperature for 24 hours, then annealed at 160°C for 10 hours, and then cooled to room temperature. The parameters of low-intensity pulsed ultrasound loading are: operating frequency 1 MHz, effective sound intensity 1 W / cm 2 When pulse ultrasound is performed, the pulse duration is 4ms and the total output is 10 min.

[0089] Comparative Example 7

[0090] BaTiO3 particles were dispersed in deionized water containing 2% w / v sodium citrate. Stirred at ambient temperature for 12 h, observed the stratification after 30 min, and then discarded the supernatant. Next, 30 mL of anhydrous ethanol was added and stirred for 30 min to form a stratified supernatant, which was repeated twice. Then deionized water was added and stirred for 30 min, and then the supernatant was separated and discarded until there was no obvious turbidity in the supernatant. The residue was thoroughly dried at 55 °C in a vacuum oven. At the same time, the L-polylactic acid powder was uniformly dissolved in trifluoroethanol at a concentration of 10%. Subsequently, BaTiO3 nanoparticles were ultrasonically dispersed in the L-polylactic acid and trifluoroethanol solution at a concentration of 3wt% and stirred for 12 h to form a uniform suspension. This suspension was then used to prepare electrospun nanofiber membranes. The electrospinning device used a 22 g metal injection needle with the needle tip 15 cm away from the center of the roller group. A static voltage of 15 kV was applied between the two. The roller receiver rotated at 2800 rpm and the spinning was completed after 8 h.

[0091] After spinning, the membrane was placed in a drying oven at room temperature for 24 hours, then annealed at 105 °C for 10 hours, annealed at 160 °C for 10 hours, and then cooled to room temperature. The parameters of low-intensity pulsed ultrasound loading were: operating frequency 1 MHz, effective sound intensity 1 W / cm 2 When pulse ultrasound is performed, the pulse duration is 4ms and the total output is 10 min.

[0092] Comparative Example 8

[0093] BaTiO3 particles were dispersed in deionized water containing 2% w / v sodium citrate. Stirred at ambient temperature for 12 h, observed the stratification after 30 min, and then discarded the supernatant. Next, 30 mL of anhydrous ethanol was added and stirred for 30 min to form a stratified supernatant, which was repeated twice. Then deionized water was added and stirred for 30 min, and then the supernatant was separated and discarded until there was no obvious turbidity in the supernatant. The residue was thoroughly dried at 55 °C in a vacuum oven. At the same time, the L-polylactic acid powder was uniformly dissolved in trifluoroethanol at a concentration of 10%. Subsequently, BaTiO3 nanoparticles were ultrasonically dispersed in the L-polylactic acid and trifluoroethanol solution at a concentration of 10wt% and stirred for 12 h to form a uniform suspension. This suspension was then used to prepare electrospun nanofiber membranes. The electrospinning device used a 22 g metal injection needle with the needle tip 15 cm away from the center of the roller group. A static voltage of 15 kV was applied between the two. The roller receiver rotated at 2800 rpm and the spinning was completed after 8 h.

[0094] After spinning, the membrane was placed in a drying oven at room temperature for 24 hours, then annealed at 105 °C for 10 hours, annealed at 160 °C for 10 hours, and then cooled to room temperature. The parameters of low-intensity pulsed ultrasound loading were: operating frequency 1 MHz, effective sound intensity 1 W / cm 2 When pulse ultrasound is performed, the pulse duration is 4ms and the total output is 10 min.

[0095] Test Case

[0096] The following shows the examination of the performance of the fiber membrane.

[0097] Each group of BaTiO3 / PLLA spinning membranes was cut into 1 cm×1 cm samples at an angle of 45°. The surface structure of the membranes was observed using a scanning electron microscope, and the average diameter of 50 fibers was quantified using ImageJ. The chemical composition and degree of crystallinity were determined by X-ray diffraction. The dispersion of BaTiO3 particles in the PLLA membrane was detected by high-resolution transmission electron microscopy. The tensile strength and Young's modulus were tested using a universal mechanical testing machine. The surface wettability was determined using a water contact angle meter.

[0098] Using quasi-static 33 The piezoelectric properties of each group were measured by an instrument and an electrometer. The catalytic degradation ability of the material was evaluated by the degradation efficiency of rhodamine B. Each group of materials was placed in a rhodamine B solution for ultrasonic treatment for different times (20, 40, 60, 80, and 100 min), and the absorption wavelength was measured by a spectrophotometer. At the same time, an electron spin resonance device was used to evaluate the ability of the spinning membrane to produce free radicals under ultrasonic stimulation. 5,5-Dimethyl-1-pyrroline-n-oxide (DMPO) can be used as a trap to capture DMPO-O2 produced during the catalytic process. - and DMPO-OH free radicals.

[0099] exist Figure 1 In the results, the X-ray diffraction spectrum (XRD) showed that compared with BTR, the BTA group had increased intensities at the (200) and (110) peaks, showing a higher degree of crystallinity. The water contact angle results showed that both BTA and BTR had lower surface wettability, which was beneficial for removal as needed during treatment. In addition, in Comparative Examples 5 and 6, only the first step annealing treatment and the second step annealing treatment were used to prepare the fiber membrane, respectively. Temperature screening found that only the first step annealing was not conducive to the enhancement of the 200 / 110 peak of the fiber membrane, and only the second step annealing was not conducive to the piezoelectric phase transformation and the peak shift to the piezoelectric phase. The performance of the fiber membrane prepared in this way was not conducive to long-term function in infectious wounds. After the two-step annealing treatment, the composite membrane exhibited stable piezoelectricity and high crystallinity (such as Figure 1 As shown in D), it is more suitable as an antibacterial healing dressing to maintain a long-term effective piezoelectric anti-infection effect.

[0100] In addition, when the fiber filaments prepared in Comparative Examples 7 and 8 were subjected to microscopic observation, it was found that when BaTiO3 nanoparticles were ultrasonically dispersed in left-handed polylactic acid at a lower concentration, the BaTiO3 nanoparticles aggregated and were unevenly distributed, and thus they were not suitable as the fiber membrane for promoting the healing of infected wounds of the present invention. On the other hand, when BaTiO3 nanoparticles were ultrasonically dispersed in left-handed polylactic acid at a higher concentration, beads and discontinuous fibers appeared, which was also not suitable as the fiber membrane for promoting the healing of infected wounds of the present invention.

[0101] Application Example 1

[0102] This application example studies the in vitro antibacterial properties of BaTiO3-doped PLLA fiber membrane driven by low-intensity pulsed ultrasound.

[0103] Staphylococcus aureus and Escherichia coli were used as representative bacteria for the evaluation of antibacterial effects. Ultrasonic irradiation (1.0W / cm², 1 MHz, 10 min) was used to fix the bacteria on the spinning membrane with 2.5% (v / v) glutaraldehyde for 4 h, gradient ethanol dehydration, and gold spraying for scanning electron microscopy imaging to observe the bacterial surface membrane structure and evaluate the damage of the spinning membrane to the bacterial morphology. In order to further evaluate the antibacterial activity of the spinning membrane, the bacteria attached to the spinning membrane were stained with SYTO9 and propidium iodide (PI) fluorescent dyes, and the bacteria were scanned by laser scanning confocal microscopy. Green fluorescence indicates live bacteria and red fluorescence indicates dead bacteria. In order to quantify the antibacterial effect, the release of bacterial intracellular proteins was detected using the Micro BCA protein detection kit. The bacteria were co-cultured in a 12-well plate for 3 days, and the formation of bacterial biofilm was detected by live / dead bacterial staining; at the same time, 0.1% (w / v) crystal violet solution was used for staining for 20 minutes, and the stained biofilm was eluted with 33% acetic acid solution, and the absorbance value was detected at a wavelength of 595 nm.

[0104] ROS can destroy the selective permeability of bacterial membrane structure by oxidizing polyunsaturated phospholipids in lipid membrane, or directly oxidize internal molecules of bacteria, leading to bacterial damage and death, and has good bactericidal properties. Ultrasound-driven BTA can interact with water molecules or oxygen to produce ROS, thereby achieving excellent antibacterial effect. In order to evaluate the antibacterial effect of each group of materials under ultrasonic irradiation, Staphylococcus aureus (Gram-positive bacteria) and Escherichia coli (Gram-negative bacteria) were selected for in vitro antibacterial effect evaluation. Figure 4A shows that the Staphylococcus aureus and Escherichia coli in the Flat group maintained normal morphology, while in the other groups, as the piezoelectric effect increased, the bacterial membranes were damaged to varying degrees, and the membrane structures shrank to varying degrees. Among them, the bacterial morphology in the BTA+US group changed significantly, the bacterial infected cell membrane structure was destroyed and shrunk, and the integrity of the cell wall and cell membrane was damaged, resulting in leakage of bacterial contents. In addition, the bacterial survival rates of Staphylococcus aureus and Escherichia coli in the BTA+US group decreased significantly ( Figure 4 B, E). The number of live bacteria in live / dead staining was significantly reduced, and the antibacterial rates against Staphylococcus aureus and Escherichia coli were as high as 88.72% and 90.43% ( Figure 5 ). The number of dead bacteria observed in the Flat group was almost negligible, indicating that the ROS produced by ultrasonic piezoelectric catalysis had considerable toxicity to bacteria, thereby effectively enhancing the antibacterial ability of bacteria. At the same time, the survival rates of Staphylococcus aureus and Escherichia coli in the ultrasonic treatment group were lower than those in the control group without ultrasonic treatment. This may be due to the cavitation effect of the huge energy released by ultrasound, which caused mechanical shear and thermal effects, causing slight damage to the bacterial membrane structure. Through quantitative analysis of bacterial protein leakage, we evaluated the degree of damage to the bacterial membrane permeability of Staphylococcus aureus and Escherichia coli when each group of materials was co-cultured with bacteria ( Figure 4 C, F). The biofilm permeability damage of Staphylococcus aureus and Escherichia coli in the BTA+US group was more serious, and the bacterial protein leakage also increased accordingly, which was consistent with the antibacterial rate results. The formation of bacterial biofilm was detected by live / dead fluorescence staining and crystal violet semi-quantitative detection. The BTA+US group had the best anti-biofilm effect ( Figure 4 D, G). This may be because the ROS generated by the piezoelectric composite membrane under ultrasound changes the permeability of the bacterial membrane by promoting lipid oxidation, ultimately leading to the leakage of bacterial contents and bacterial death.

[0105] Application Example 2

[0106] This application example studies the biocompatibility of BaTiO3-doped PLLA fiber membrane driven by low-intensity pulsed ultrasound.

[0107] L929 fibroblasts were selected and seeded on the spinning membrane. They were cultured in a solution supplemented with 10% (v / v) fetal bovine serum (FBS) and 1% (v / v) penicillin-streptomycin at 37°C and 5% CO2. CCK-8 was used to evaluate cell proliferation after 1, 2, and 3 days of culture, and ultrasound irradiation (1.0 W / cm², 1 MHz, 10 min) was used every day. Live / dead cell staining kit was used to detect cell viability after 1, 2, and 3 days of culture to evaluate the cytotoxicity of the material. Live cells were labeled with green fluorescence using calcein dye, and dead cells were labeled with red fluorescence using PI dye. Cell staining was observed under CLSM. The scratch test was used to detect the effects of ultrasound stimulation and BaTiO3 / PLLA on the migration ability of L929 fibroblasts. ImageJ software quantified the cell migration rate by comparing the pixel coverage at each time point in the scratch area.

[0108] The CCK8 test results on the 1st, 2nd and 3rd days showed that under ultrasound drive, the cell viability of all groups was greater than 90% ( Figure 6 C). In the live / dead staining experiment, live cells were stained green and dead cells were stained red, which also showed good cell viability, indicating that the material has good biocompatibility ( Figure 6 A).

[0109] In addition, if Figure 6 As shown in Figure 2, the cell migration speed in the BTA+US group was the fastest, and the wound coverage rate was about 98.37% after 24 h of culture. The wound coverage rates of Flat+US and BTR+US in the non-piezoelectric group and weak piezoelectric group were 19.18% and 27.88%, respectively, indicating that the ultrasound effect can promote the migration of fibroblasts for wound repair ( Figure 6 B). This is attributed to the combined effects of ultrasound-induced cavitation and physical stimulation factors such as mechanical stress and electric field changes caused by the barium titanate-doped polylactic acid film.

[0110] Application Example 3

[0111] This application example studies the performance of low-intensity pulsed ultrasound-driven BaTiO3-doped PLLA fiber membrane in promoting the healing of infected skin defects in vivo.

[0112] To investigate the effect of spinning membrane on promoting the healing of infected wounds under ultrasound stimulation, a mouse full-thickness dermal wound infection model was established. After 8-week-old male BalB / c mice were completely anesthetized, two circular full-thickness skin wounds (𝜑=6mm) were made on the back, and 20 μL of Staphylococcus aureus suspension was applied to the wounds. The infected wounds of mice were successfully established by fixing with 3M dressing for 48 h. Subsequently, the infected skin wounds were covered with spinning membranes and fixed on the back with 3M dressings. Ultrasound treatment (1.0 W / cm², 1 MHz, 10 min) was given every 2 days. The wound sizes were measured and recorded on the 2nd, 4th, 6th, 8th, and 10th days, and the wound healing rate was calculated using Image J software. The mice were killed on the 4th and 10th days, respectively, and the infected skin tissues around the wounds of mice in each group were obtained. The above tissue samples were subjected to hematoxylin-eosin (HE) staining, Masson trichrome staining, immunofluorescence staining, and qPCR detection to evaluate the wound healing and epithelial regeneration effects.

[0113] The non-piezoelectric film was used as the control group (Flat), and the trajectory of wound healing was recorded at different times from day 0 to day 10 ( Figure 7 B, C). Figure 7 As shown in D, the wound healing rate of the BTA+US group on the 10th day was 95.52%, which was the best wound repair effect among all groups, indicating that the ROS generated by the piezoelectric effect triggered by US had strong bactericidal ability and improved wound healing in vivo. The wound healing of the Flat group was slow, with a wound healing rate of 57.37% on the 10th day.

[0114] To further analyze epidermal regeneration and wound repair, Figure 7 As shown in the HE staining results in E, compared with the other groups, the BTA+US group had less granulation tissue, fewer inflammatory cells, thinner epithelium, and richer hair follicle structure in the epithelium, while the Flat group had incomplete epithelium and a large number of inflammatory cells ( Figure 7 E, F). This suggests that BTA combined with ultrasound treatment significantly accelerates wound closure and inhibits inflammatory response. In addition, the degree of skin regeneration in the BTA group and Flat+US group was better than that in the Flat group, which also proves that ultrasonic mechanical stimulation and the porous structure of the fiber membrane are conducive to the spreading and migration of the cytoskeleton, accelerating the healing of infected wounds. Figure 7 As shown in G, Masson staining results showed that compared with other groups, the collagen structure of the BTA+US group was the densest on the 10th day, with relative collagen deposition of 38.79% and 75.12%, respectively, which improved the wound healing efficiency ( Figure 7 H).

[0115] like Figure 8As shown in A, the pro-inflammatory cytokines in the wound of the BTA+US group were less than those in the other groups, indicating that the piezoelectric effect of BTA under ultrasound irradiation significantly reduced the inflammatory reflex and played a role in sterilization and anti-infection. In addition, the wound of the BTA+US group had a wider area of ​​KRT5 and CD31 positive staining, and the new epithelial and angiogenesis rates were the best compared with other groups. This may be due to the synergistic effect between the antibacterial activity of ROS generated by the ultrasound piezoelectric effect and tissue regeneration ( Figure 8 BD).

[0116] On the 10th day, PCR was used to detect the expression of pro-inflammatory factors such as TNFα, iNOS, and IL-1 in the lesions. The results showed that the expression of pro-inflammatory factors in the BTA+US group was significantly lower than that in the other groups, which was consistent with the above results ( Figure 8 EG). This indicates that the BTA+US group reduces inflammation of the infected wound surface and is beneficial to the repair and healing of the wound surface. In addition, the performance of the membrane material prepared by the present invention is better than that of the same type of membrane material ( Figure 8 H).

[0117] In summary, the BaTiO3-doped PLLA electrospun fiber membrane obtained by the present invention can generate reactive oxygen on the membrane surface, and exhibits a good antibacterial effect in infected skin wounds through ultrasound-mechanical-electric conversion. This process not only regulates cell behavior and cytoskeleton expansion, but also promotes spontaneous wound closure without the need for additional drugs. It can be removed as needed during the treatment process without causing tissue adhesion. It has been verified that the fiber membrane of the present invention effectively healed open wounds infected with Staphylococcus aureus in a mouse model within 10 days under ultrasound drive, reduced inflammation, promoted re-epithelialization and angiogenesis, and effectively closed the wound autonomously.

[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. Application of fiber membrane in the preparation of materials for promoting healing of infected skin wounds, characterized in that: The fiber membrane comprises a plurality of non-randomly arranged spun nanofibers and inorganic nanoparticles, wherein the spun nanofibers are prepared by electrostatic spinning of a material comprising L-polylactic acid, and the inorganic nanoparticles are selected from at least one of barium titanate, barium strontium titanate, strontium titanate, lithium niobate and potassium sodium niobate, and the fiber membrane is prepared by the following steps: (1) dissolving L-polylactic acid in an organic solvent to obtain a L-polylactic acid solution, dispersing inorganic nanoparticles in the L-polylactic acid solution, wherein the concentration of the inorganic nanoparticles in the L-polylactic acid solution is 5.2-8.8 wt %; (2) using the L-polylactic acid solution to perform electrospinning to obtain a fiber membrane; (3) annealing the fiber membrane; (4) The fiber membrane is subjected to pulse ultrasonic treatment, wherein the pulse ultrasonic treatment conditions include: effective sound intensity of 0.20-2.50 W / cm 2 , ultrasonic frequency 0.5-4MHz, pulse duration 1-10ms, total output 5-20min.

2. The use according to claim 1, characterized in that: The receiving end of the spinning is a roller, and the non-random arrangement is achieved by controlling the rotation speed of the receiving roller, and the rotation speed is 2000-5000rpm.

3. The use according to claim 1, characterized in that: The annealing treatment includes: annealing the fiber membrane at 100-110° C. for 8-12 hours, naturally cooling to room temperature, and then annealing at 155-165° C. for 8-12 hours and then naturally cooling to room temperature.

4. Use of a fiber membrane and an ultrasonic generator in the preparation of a medical device for healing infected skin wounds, characterized in that: The fiber membrane comprises a plurality of non-randomly arranged spun nanofibers and inorganic nanoparticles, wherein the spun nanofibers are prepared by electrostatic spinning of a material comprising L-polylactic acid, and the inorganic nanoparticles are selected from at least one of barium titanate, barium strontium titanate, strontium titanate, lithium niobate and potassium sodium niobate, and the fiber membrane is prepared by the following steps: (1) dissolving L-polylactic acid in an organic solvent to obtain a L-polylactic acid solution, dispersing inorganic nanoparticles in the L-polylactic acid solution, wherein the concentration of the inorganic nanoparticles in the L-polylactic acid solution is 5.2-8.8 wt %; (2) using the L-polylactic acid solution to perform electrospinning to obtain a fiber membrane; (3) annealing the fiber membrane; The ultrasonic generator is configured to perform pulse ultrasonic treatment on the fiber membrane. The pulse ultrasonic treatment conditions include: effective sound intensity of 0.20-2.50 W / cm 2 , ultrasonic frequency 0.5-4MHz, pulse duration 1-10ms, total output 5-20min.

5. The use according to claim 4, characterized in that: The receiving end of the spinning is a roller, and the non-random arrangement is achieved by controlling the rotation speed of the receiving roller, and the rotation speed is 2000-5000rpm.

6. The use according to claim 4, characterized in that: The annealing treatment includes: annealing the fiber membrane at 100-110° C. for 8-12 hours, naturally cooling to room temperature, and then annealing at 155-165° C. for 8-12 hours and then naturally cooling to room temperature.

Citation Information

Patent Citations

  • Preparation method of heart regeneration patch material based on piezoelectric nano-generator

    CN115352164A

  • Preparation method of pressure-sensitive nanofiber membrane for wound dressing

    CN116043413A

  • Biodegradable antibacterial piezoelectric wound dressing

    US20210378949A1

  • Biodegradable piezoelectric composite materials

    US20210379249A1